Perfusion Parameter Thresholds That Discriminate Ischemic Core Vary with Time from Onset in Acute Ischemic Stroke - Yoshie, T.; Yu, Y.; Jiang, H.; Honda, T.; Trieu, H.; Scalzo, F.; Saver, J.L.; Liebeskind, D.S.; on behalf of the UCLA Reperfusion Therapy Investigators (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: When mapping the ischemic core and penumbra in patients with acute ischemic stroke using perfusion imaging, the core is currently delineated by applying the same threshold value for relative CBF at all time points from onset to imaging. We investigated whether the degree of perfusion abnormality and optimal perfusion parameter thresholds for defining ischemic core vary with time from onset to imaging.MATERIALS AND METHODS: In a prospectively maintained registry, consecutive patients were analyzed who had ICA or M1 occlusion, baseline perfusion and diffusion MR imaging, treatment with IV tPA and/or endovascular thrombectomy, and a witnessed, well-documented time of onset. Ten superficial and deep MCA ROIs were analyzed in ADC and perfusion-weighted images.RESULTS: Among the 66 patients meeting entry criteria, onset-to-imaging time was 162 minutes (range, 94–326 minutes). Of the 660 ROIs analyzed, 164 (24.8%) showed severely or moderately reduced ADC (ADC <= 620, ischemic core), and 496 (75.2%), mildly reduced or normal ADC (ADC > 620). In ischemic core ADC regions, longer onset-to-imaging times were associated with more highly abnormal perfusion parameters–relative CBF: Spearman correlation, r = –0.22, P = .005; relative CBV: r = –0.41, P < .001; MTT: – r = –0.29, P < .001; and time-to-maximum: r = 0.35, P < .001. As onset-to-imaging times increased, the best cutoff values for relative CBF and relative CBV to discriminate core from noncore tissue became progressively lower and overall accuracy of the core tissue definition increased.CONCLUSIONS: Perfusion abnormalities in ischemic core regions become progressively more abnormal with longer intervals from onset to imaging. Perfusion parameter value thresholds that best delineate ischemic core are more severely abnormal and have higher accuracy with longer onset-to-imaging times.AUCarea under the ROC curveOTIonset to imagingrCBFrelative cerebral blood flowrCBVrelative cerebral blood volumeROCreceiver operating characteristicTmaxtime-to-maximum